2021
DOI: 10.1016/j.jecp.2020.105008
|View full text |Cite
|
Sign up to set email alerts
|

When correlation equals causation: A behavioral and computational account of second-order correlation learning in children

Abstract: We examined 2-and 3-year-old children's ability to use second-order correlation learning-in which a learned correlation between two pairs of features (e.g., A and B, A and C) is generalized to the noncontiguous features (i.e., B and C)-to make causal inferences. Previous findings showed that 20-and 26-month-olds can use second-order correlation learning to learn about static and dynamic features in category and non-category contexts. The present behavioral study and computational model extend these findings to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Coming to understand the world in ways that support effective reasoning, accurate prediction, and adaptive behavior requires keen attunement to causality. Accordingly, perception of physical causality emerges early (Mascalzoni et al, 2013; Oakes & Cohen, 1995), and an extensive literature describes children’s rapidly-developing abilities to infer causality more broadly from patterns of covariation and the outcomes of active interventions (e.g., Benton et al, 2021; Goddu & Gopnik, 2020; Goddu et al, 2021; Gopnik et al, 2001). Not only are young children capable of perceiving and reasoning about causality, but they appear to have a strong intrinsic motivation to acquire causal understanding of the world around them.…”
mentioning
confidence: 99%
“…Coming to understand the world in ways that support effective reasoning, accurate prediction, and adaptive behavior requires keen attunement to causality. Accordingly, perception of physical causality emerges early (Mascalzoni et al, 2013; Oakes & Cohen, 1995), and an extensive literature describes children’s rapidly-developing abilities to infer causality more broadly from patterns of covariation and the outcomes of active interventions (e.g., Benton et al, 2021; Goddu & Gopnik, 2020; Goddu et al, 2021; Gopnik et al, 2001). Not only are young children capable of perceiving and reasoning about causality, but they appear to have a strong intrinsic motivation to acquire causal understanding of the world around them.…”
mentioning
confidence: 99%
“…The third account of a sole ontogenetic origin to causal representations is that causality is a counterfactual-supporting dependence relation inferred from patterns of covariation (Chaput & Cohen, 2001). Such accounts are usually examined more in the context of adult causal reasoning (Cheng, 1997;Pearl, 2000) or causal learning in 2-4-year-old children (Benton, Rakison, & Sobel, 2021;Gopnik, Sobel, Schulz, & Glymour, 2001;Gopnik et al, 2004).…”
Section: The Ontogenetic Origins Of Representations Of Causementioning
confidence: 99%
“…Note this entire description would be the mechanism of how second-order correlation learning might unfold, from the start stage to the final stage, to enable children to know that the test object with the purple diamond on it is causally efficacious. Benton et al (2021) found that children activated the machine with the test object that possessed the purple diamond but not with the test object that possessed the yellow circle. Given that there was no other basis on which to choose between the two test objects other than the embodied second-order correlations, this finding supported the idea that children's causal inferences were based on second-order correlation learning.…”
Section: Example Of a Developmental Mechanism Of Cognitive Changementioning
confidence: 99%
“…To illustrate how this definition can be used to construct complete definitions of developmental mechanisms of cognitive change, consider second‐order correlation learning as one example of such a mechanism (Benton et al, 2021; Rakison & Benton, 2019; Yermolayeva & Rakison, 2016). This is a domain‐general, associative‐learning mechanism that enables learners to detect the relation between non‐contiguously presented features and cues.…”
Section: Example Of a Developmental Mechanism Of Cognitive Changementioning
confidence: 99%
See 1 more Smart Citation